2015
DOI: 10.1007/s10750-014-2159-z
|View full text |Cite
|
Sign up to set email alerts
|

Age and origin of Australian Bennelongia (Crustacea, Ostracoda)

Abstract: South-western Australia holds an exceptional number of endemic taxa and has been recognized as a biodiversity hotspot at a global scale. We report a much higher diversity in the genus Bennelongia (Ostracoda) in Western than in eastern Australia. Using mitochondrial COI sequence data for phylogenies, relative age estimates, lineage-through-time plots, and reconstructions of ancestral distributions, we test four hypotheses that might explain the higher diversity and endemicity in Western Australia. (1) We find n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…For example, in the family Cyprididae, distances between 18S sequences vary from 2% (within genus) to 11% (between genera) (Kong et al 2014); while in Polycopidae the same marker has approximately 3% intragenic and 10% intergeneric variability (Tanaka et al 2014; Karanovic et al 2016). The distances between COI sequences of the four Baikal candonids are within the range of those observed for other ostracods and crustaceans in general (Lefébure et al 2006; Schön and Martens 2012; Schön et al 2015, 2017). …”
Section: Discussionsupporting
confidence: 76%
“…For example, in the family Cyprididae, distances between 18S sequences vary from 2% (within genus) to 11% (between genera) (Kong et al 2014); while in Polycopidae the same marker has approximately 3% intragenic and 10% intergeneric variability (Tanaka et al 2014; Karanovic et al 2016). The distances between COI sequences of the four Baikal candonids are within the range of those observed for other ostracods and crustaceans in general (Lefébure et al 2006; Schön and Martens 2012; Schön et al 2015, 2017). …”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, this ostracod showed different patterns of distribution between the two habitat types in damp sediment in different wetlands, although the effect of the drying treatment was the same across all wetlands. Recent research shows that the genus Bennelongia has high levels of cryptic diversity in south-western Australia (Schon et al 2015), so it is possible that the variable distribution patterns we observed among wetlands were caused by inadvertently pooling more than one Bennelongia species.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, a study based on 18S rRNA stipulated a high incongruence between fossil and molecular divergence time estimates in this group, partly due to the controversial taxonomy of fossil ostracods (Tinn & Oakley, 2008). Consequently, studies attempting to estimate divergence times in ostracods mostly applied universal invertebrate COI molecular clock rates proposed by Wilke, Schultheiß, and Albrecht (2009) (see Schön, Shearn, Martens, Koenders, & Halse, 2015), or rates calculated for some ostracod lineages (Schön, Martens, van Doninck, & Butlin, 2003) based on COI and ITS markers. The study of the evolutionary history and phylogenetic relationships of Lake Baikal and Lake Tanganyika Cytherocopina by Schön and Martens (2012) exerted several dating methods in order to compare the divergence times of this ostracod group in two ancient lakes.…”
mentioning
confidence: 99%